RELIGIOUS CHARACTER EDUCATION LEARNING PATTERN AT UPT SD NEGERI KALIPANG 01 - Rarasati, Ida Putri; Baihaqi, M. Iqbal; Mahfudi, Yuswita Hamdan (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This study aimed to determine the application pattern of religious character education at UPT SD Negeri Kalipang 01. This type of research is qualitative and descriptive. The subjects of this study were UPT SD Negeri Kalipang 01's principals, teachers, and students. According to the findings of the study, the pattern of application of religious character education at UPT SD Negeri Kalipang 01 utilized a system of application and habituation in the learning process, intracurricular and extracurricular activities, and habituation through school culture. The implementation of exemplary and habituation strategies is supported by advice, attention/supervision, rewards, and punishments. Developed religious character values are devotion, tolerance, and living in harmony. Existing supporting infrastructure includes houses of worship, religious equipment, and holy texts. Lack of infrastructure and ignorance about worship are the obstacles encountered. The solution is to add school facilities and infrastructure and to teach the significance of religion. The pattern of applying religious character education at UPT SD Negeri Kalipang 01 has a positive effect, as students become more devout in their worship and more tolerant.